Analysis of the p53 gene by PCR-SSCP in ten cases of Wilms’ tumor - Defavery, Ricardo; Lemos, José Alexandre Rodrigues; Kashima, Simone; Bernardes, José Eduardo; Scridelli, Carlos Alberto; Covas, Dimas Tadeu; Tone, Luiz Gonzaga (São Paulo Medical Journal, 2000)
CONTEXT: Mutations of the p53 tumor suppressor gene are the most frequent alterations observed in human neoplasias affecting adults. In pediatric oncology, however, they have seldom been identified. Wilms’ tumor is a renal neoplasia commonly occurring in children and is associated with mutations of the WT1 gene. The correlation between Wilms’ tumor and alterations of the p53 gene has not been well established, with a low frequency of mutations having been reported in this type of tumor. Mutation may be associated with advanced stage disease and unfavorable histology. OBJECTIVE: To screen for mutations of the p53 gene by the PCR-SSCP method and DNA sequencing in cases of Wilms’ tumor sug-gestive of mutation. DESIGN: Case Report. CASE REPORT: Evaluations of exons 5-9 of the p53 gene in DNA samples extracted by PCR-SSCP from 10 Wilms’ tumors in children at different stages, and DNA sequencing. Changes in SSCP analy-sis were observed in exon 8 in two samples. The probable muta-tions were not confirmed by DNA sequencing. The absence of point mutations in p53 gene observed in the 10 samples of Wilms’ tumor studied agrees with literature data, with DNA sequencing being of fundamental importance for the confirmation of possible mutations.